2008
DOI: 10.1111/j.1475-6765.2008.00777.x
|View full text |Cite
|
Sign up to set email alerts
|

Immigration as a political issue in Denmark and Sweden

Abstract: Abstract.  Studies of party politics and party competition in West European democracies all point to diversification. Non‐economic issues such as the environment, refugees and immigrants or law and order have become increasingly central to party politics. However, there has been surprisingly little interest in explaining variation across time and countries concerning which issues actually become central to party competition. From the sparse literature, two general answers can be discerned. One is societal, foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
164
0
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(175 citation statements)
references
References 32 publications
5
164
0
6
Order By: Relevance
“…Parties on the left are often torn between the preferences of their traditional working class base, which is often weary of immigration, and the better educated middle-class partisans who favor liberal immigration policies. An example of this can be seen in Danish party competition where the Social Liberals are on the right of the Social Democrats on the left-right dimension, but advocate less restrictive immigration policies (Green-Pedersen and Krogstrup 2008). However, in other party systems, this "lack of fit" may be less obvious in party competition since mainstream parties will seek to avoid mobilizing wedge issues that have the potential to drive a wedge between factions in a party or between parties in a coalition.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Parties on the left are often torn between the preferences of their traditional working class base, which is often weary of immigration, and the better educated middle-class partisans who favor liberal immigration policies. An example of this can be seen in Danish party competition where the Social Liberals are on the right of the Social Democrats on the left-right dimension, but advocate less restrictive immigration policies (Green-Pedersen and Krogstrup 2008). However, in other party systems, this "lack of fit" may be less obvious in party competition since mainstream parties will seek to avoid mobilizing wedge issues that have the potential to drive a wedge between factions in a party or between parties in a coalition.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…In others, the issue registers temporarily on their electoral radar screen, only to drop off it at subsequent elections (see e.g. Green-Pedersen and Krogstrup, 2008;Pellikann et al, 2007;Cornelius et al, 1994;Thränhardt, 1995). This variance constitutes a puzzle for the study of electoral politics.…”
mentioning
confidence: 99%
“…Akirav, Cox and McCubbins (2010) found that in the Knesset the opposition parties' roll rates on exceptional bills such as the budget are higher than their roll rates on ordinary bills. Green-Pedersen and Krogstrup (2008) claimed that in the competition for voters, legislative bills are one way to signal one's priorities to the public.…”
Section: The Definition and Role Of The Oppositionmentioning
confidence: 99%
“…Numerous studies have investigated the strength of the opposition in a variety of countries worldwide (e.g., Green-Pedersen & Krogstrup, 2008;Helms, 2008b;Kaiser, 2008;Proksch & Slapin, 2011;Salmond, 2004;Schrire, 2008;Tuttnauer, 2013;Wondwosen, 2009). However, Israel is one country in which there has been little research interest in the opposition (Akirav, Cox, & McCubbins, 2010;Friedberg & Hazan, 2009;Tuttanuer, 2013).…”
Section: The Definition and Role Of The Oppositionmentioning
confidence: 99%